AQUATIC PHYCOMYCETES AND ASCOMYCETOUS FUNGI ISOLATED FROM ARTEMISIA ANNUA L. PLANTATION SOIL IN A NIGERIAN UNIVERSITY - Ogbonna, A. I.; Onwuliri, F. C.; Ogbonna, C. I. C.; Chuku, A. (European Scientific Journal, ESJ, 2015)
Survey was carried out on the ascomycetous and aquatic fungi present in the soil of University of Jos Artemisia annua Plantation in Gangnum, Langtang South Local Government Area of Plateau State. Portions of the soil samples collected from three (3) locations were steamed in glass beaker placed in a steamer for 4-10 minutes at 100o C before inoculation. Fungal isolation was carried out using soil plate method incubated at 25 ± 2o C. Aquatic phycomycetes were isolated using baits. Two (2) genera of aquatic phycomycetes were isolated, including Achyla dubia and Allomyces arbuscular. Fifty–eight ascomycetous fungi were also isolated from the soil samples. The predominant ascomycetous fungi isolated include among others; Chaetomium bastrychodes, C. cancriodeum, C. cochloides, C. globosum, C. nigricolor, C. senegalensis, C. spirale, Aspergillus candidus A. flavus, A. fumigatus , A. glaucus, A. nidulans, A. niger, A. oryzae, A. terreus, F. avenaceum, F. oxysporum, F. roseum, F. solani, F. sporitrichioides, Penicillium chrysogenum, P. citrinum, P.notatum, P.expansum, Trichoderma harzianum, T. piluliferum, Alternaria alternata, Aureobasidium pullulans, Botrytis cinerea, Cladosporium sp, Curvularia lunata, Scopulariopsis sp, Torula herbarum, Unidentified sp and a Basidiomycete. The physico-chemical properties of the soil samples were found to be varied, and were found to affect the distribution and population of fungi. The soil was found to be high in organic matter content which could have been as a result of activities of the species of fungi numerous in the soil. The implications of the results are discussed.